Multilevel Structural Characteristics of Jinshajiang Main Fault and Its Influence on Engineering - Hui Zhou; Yihuan Shen; Yong Zhu; Gang Han; Chuanqing Zhang; Ning Zhang (Advances in Materials Science and Engineering)
It is of great significance to study the geological characteristics of faults and the corresponding displacement patterns for the tunnel engineering crossing active faults. On the basis of field investigation and geological data analysis, it is found that the secondary weak structures, such as narrow cleavage bands, narrow joint bands, fault gouge zones, and small folds, often appear in the fault fracture zones and affected zones. The multilevel structure of fault is proposed from mechanics and engineering by summarizing their main characteristics. Taking the outcrop of fracture zones of Batang section, Jinshajiang main fault in the Qinghai-Tibet Plateau as the research object, the geometric characteristics of rock masses, the particle size, mineral composition, and mechanical characteristics of rocks in the fault are studied through field investigation, geological mapping, mineral composition analysis, and mechanical tests. In addition, a displacement model of multilevel structure fault is presented by numerical simulation. The results show that the Jinshajiang main fault comprises a primary structure and several secondary weak structures, which has a typical structure of multilevel fault. There are several secondary weak structures in the outcrop of the fracture zone. Compared with the rock masses in the primary structure, the joints of the rock masses in the secondary weak structure are more developed, and the rock particle size is smaller, the mud content is higher, and the mechanical strength is lower. The geometric morphology, mineral composition, and mechanical properties of the rock masses in the secondary weak structure are obviously different from those of the primary structure. The overall displacement mode of multilevel structural fault is S-shaped distribution, and the secondary weak structure will affect the displacement distribution pattern and have the possibility of sliding when the fault moves. Therefore, the secondary weak structure section in the tunnel should be a priority for prevention and control when designing tunnels through active faults. The multilevel structure of the fault, together with centralized structure, distributed structure, and stepped structure of the fault, can be used as a structure classification method of fault structure, which provides a reference for the study of disaster mechanisms, and prevention and control measures of tunnels crossing active faults.